CHARACTERIZATION OF THE ACCRETED OPHIOLITE SLICES OF RUTLAND ISLAND, ANDAMAN SEA: EVOLUTION IN A SUPRASUBDUCTION ZONE SETTING - Bhattacharya, Anindya; Pal, Tapan; Ghosh, Biswajit (Ofioliti, 2013)
Detailed mapping of a rocks110 km2 area of the Rutland Island has demarcated four dismembered thrust slices of Cretaceous ophiolite which are interleaved with Eocene sediments. The ophiolite sequence is represented by tectonite, chromitite pods, transitional peridotite, layered ultramafic-mafic, intrusives of plagiogranite-diorite suite and extrusives of basalt and boninite, capped by pelagic sediments. The layered ultramafics and the massive chromitites are characterized by high Mg-olivine (Fo92-93), high Mg-orthopyroxene (En88–90), low CaO (XCaM2 = 0.01 to 0.03), low alumina (Al2O3 = 0.66 to 1.20 wt %) and high Cr-chromites, which is typical of boninitic melts in suprasubduction zone (SSZ) environments. The estimated Al2O3 contents of the parental melt (10.80 wt%) correspond to a boninitic parental melt. The Type-2 low-Ca boninite extrusives with SiO2 < 58 wt%, MgO = 8.4 to 9.5 wt% is the extrusive equivalent of boninitic parental lava. As boninitic rocks show higher depletion of Zr and Y than the basaltic rocks, the source rock for boninite was more depleted than that of basalts. Tectonites showing embayed clinopyroxene grains and irregular shaped Cr-spinel as residual phases preserve records of partial melting. The degree of partial melting of the mantle tectonite has been estimated as 20%, based on Cr content of the spinel. Petrographic features of the transitional peridotites show dissolution of orthopyroxene and clinopyroxene grains and development of small fresh olivine grains along the embayed margins and fractures, displaying melt-rock interaction effects in the mantle rocks. The melt-rock interaction features as well as the bivariant relation of TiO2 wt% vs. Al2O3 wt% of the chromites reflect the evolution of the Rutland ophiolite in a SSZ setting.